Human airway organoids as 3D in vitro models for a toxicity assessment of emerging inhaled pollutants: Tire wear particles - Jiang, Yingying; Lu, Lin; Du, Chao; Li, Yanting; Cheng, Wenting; Bi, Huanhuan; Li, Guo; Zhuang, Min; Ren, Dunqiang; Wang, Hongmei; Ji, Xiaoya (Frontiers in Bioengineering and Biotechnology, 2023)
The three-dimensional (3D) structured organoids have become increasingly promising and effective in vitro models, and there is an urgent need for reliable models to assess health effects of inhaled pollutants on the human airway. In our study, we reported human airway organoids (hAOs) for toxicity assessment of TWPs as the emerging inhaled pollutant. We induced primary human bronchial epithelial cells (HBECs) to generated hAOs, which recapitulated the key features of human airway epithelial cells including basal cells, ciliated cells, goblet cells and club cells. Tire wear particles (TWPs) generated by the wearing of tire treads were considered as an emerging major source of inhaled road traffic-derived non-exhaust particles, but their health effect on lung is poorly understood. Here, we used hAOs to assess the toxicology of TWPs on human airway. In exposure study, the inhibitory effect of TWPs on hAOs growth was observed. TWPs induced significant cell apoptosis and oxidative stress in a dose-dependent manner. In qPCR, TWPs significantly up-regulated the genes expression involved in inflammation response. Additionally, TWPs exposure reduced SCGB1A1 gene expression associated with the function of the club cell and KRT5 gene expression related to the function of the basal cells. In conclusion, this was first study using hAOs for the toxicological assessment of TWPs, and our findings revealed that hAOs provide the evaluation model of inhaled pollutants potentially affecting the lungs.